2004
DOI: 10.1038/sj.emboj.7600087
|View full text |Cite
|
Sign up to set email alerts
|

XRCC3 deficiency results in a defect in recombination and increased endoreduplication in human cells

Abstract: XRCC3 was inactivated in human cells by gene targeting. Consistent with its role in homologous recombination, XRCC3(-/-) cells showed a two-fold sensitivity to DNA cross-linking agents, a mild reduction in sister chromatid exchange, impaired Rad51 focus formation and elevated chromosome aberrations. Furthermore, endoreduplication was increased five- seven-fold in the mutants. The T241M variant of XRCC3 has been associated with an increased cancer risk. Expression of the wild-type cDNA restored this phenotype, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
72
3

Year Published

2004
2004
2013
2013

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(82 citation statements)
references
References 55 publications
7
72
3
Order By: Relevance
“…In contrast, depletion of XRCC3 transcription by siRNA in MCF7 cells inhibited cell proliferation, led to accumulation of DNA breaks and triggered activation of the p53-dependant cell death (40). XRCC3 deficient HCT116 cells have shown increased sensitivity to cisplatin and mitomycin C (42). Although some studies have shown no association between polymorphisms in XRCC3 and colorectal cancer risk (43)(44)(45)(46) other studies have (47,48), and in addition XRCC3 polymorphisms have also been associated with breast and lung cancer susceptibility (41,49).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, depletion of XRCC3 transcription by siRNA in MCF7 cells inhibited cell proliferation, led to accumulation of DNA breaks and triggered activation of the p53-dependant cell death (40). XRCC3 deficient HCT116 cells have shown increased sensitivity to cisplatin and mitomycin C (42). Although some studies have shown no association between polymorphisms in XRCC3 and colorectal cancer risk (43)(44)(45)(46) other studies have (47,48), and in addition XRCC3 polymorphisms have also been associated with breast and lung cancer susceptibility (41,49).…”
Section: Discussionmentioning
confidence: 99%
“…Although these findings might suggest that the LOH mechanism in spontaneous tumors can be influenced by Rad54 inactivation, the sample size was too small to justify any mechanistic hypothesis. However, increased frequency of aneuplody, related to centrosome abnormalities, has also been observed in cells defective for other recombination genes such as BRCA1, BRCA2, XRCC2, XRCC3 and Rad51 paralogue family (Tutt et al, 1999;Xu et al, 1999;Griffin et al, 2000;Deans et al, 2003;Yoshihara et al, 2004;Smiraldo et al, 2005).…”
Section: Effect Of Rad54 and Dnapkcs Deficiency On Ptc1 Loh In Full-bmentioning
confidence: 99%
“…Our results show that the Rad51C-deficient HeLa cells display ϳ2-fold greater sensitivity to MMC using acute treatment, demonstrating that these cells have a similar phenotype for MMC sensitivity to that of the chicken and hamster mutants. An XRCC3 gene knockout in the human colon cancer cell line HCT116 has been reported recently, and the XRCC3-deficient cells showed ϳ2-fold excess sensitivity to MMC (58 (59,60) that is associated primarily with the late S/G 2 phase (49). By contrast, the NHEJ-defective Chinese hamster ovary mutants for XRCC4, Ku86, and DNA-PKcs (the XR-1, xrs5/6, and V3 cell lines, respectively) are highly sensitive to IR in G 1 and early S phases compared with the wild type but are more IR-resistant in late S/G 2 (61)(62)(63)(64).…”
Section: Rad51c Dynamically Influences the Protein Levels Of Other Rad51mentioning
confidence: 99%